Laparoscopic laser cholecystectomy: results of the technique in 210 patients. - Scott, A. D. (Royal College of Surgeons of England, 1992)
The results of laparoscopic laser cholecystectomy (LLC) in a consecutive series of 210 patients, operated on between May 1990 and August 1991, were assessed to analyse the advantages of the technique and to detail the causes of any technical problems, failures, or complications. The operations were performed by JMcKW and ADNS. A success rate of 98% (206/210) was achieved with a minor complication rate of 13% (26/210) and major complication rate of 3% (7/206), including three patients (3/206; 1.5%) who had a reactionary haemorrhage postoperatively, two requiring laparotomy. The length of hospital stay was 48 h or less in over 80% (148/184) of the patients. The period of absence from work was 2 weeks or less in over 90% (118/130) of the patients. Cholecystectomy can safely be performed laparoscopically and this procedure has significant advantages over open cholecystectomy.